Copper Induces Damage, Oxidative Stress and Cell Death in Endothelium of Chronic Intoxicated Wistar Rats - Fernández Rodarte, Bernardo Alfonso; Soto Domínguez, Adolfo; González Navarro, Alejandro; Mellado Ayala, Maximiliano; Piña Mendoza, Edgar; Rodríguez Rocha, Humberto; Montes de Oca Luna, Roberto; Guerra Leal, Jesús Dante (2022)
Reactive Oxygen Species (ROS) are part of the functional balance of various systems, they can generate cellular damage by oxidative stress associated with disease processes such as atherosclerosis, cardiovascular disease, diabetes, and aging. Some studies report that copper induces damage to the endothelium, which could be associated with cardiovascular pathologies. This study was an experimental comparative, prospective, longitudinal, and controlled clinical trial in a murine animal model. Twenty-four male Wistar rats were included, the distribution of the groups was time-depending chronic exposition to copper, and a control group. Results show gradual alterations in the groups treated with copper: areas with loss of the endothelium, signs of disorganization of smooth muscle fibers in the tunica media, as well as areas with the fragmentation of the elastic sheets. A significant statistical difference was observed in the active- Caspase-3 analysis expression in the aortic endothelium and endothelium of the capillaries and arterioles of the lung between the control group vs 300 ppm of copper. Expression of eNOS was detected in the endothelium of the aorta and vessels of the lung. Our study shows histological changes in the walls of the great vessels of intoxicated rats with copper, and the increment of inflammatory cells in the alveoli of the study model, mainly at a high dose of copper exposition. These results will be useful to understand more about the mediators involved in the effect of copper over endothelium and cardiovascular diseases in chronic intoxication in humans